Hepatitis C Eradication and Improvement of Cryoglobulinemia-Associated Rash and Membranoproliferative Glomerulonephritis with Interferon and Ribavirin after Kidney Transplantation - Marilyn Zeman; Patricia Campbell; Vincent G Bain (Canadian Journal of Gastroenterology)
Postrenal transplant hepatitis C is increasing in frequency due to the high prevalence of hepatitis C among patients with renal failure. Despite this, there is still no standard hepatitis C treatment available for renal transplanted recipients. Combination antiviral hepatitis C therapy, the standard of care in the nontransplant population, is generally avoided because of documented renal graft rejection secondary to interferon treatment. A case of a male patient with postrenal transplant hepatitis C, which was associated with cryoglobulinemia and glomerulonephritis of the graft, is presented. He was treated with standard interferon with ribavirin. Sustained viral clearance was achieved despite ongoing evidence of cryoglobulinemia. Renal function, which had been deteriorating before treatment, improved as evidenced by the stabilization of serum creatinine and marked improvement of proteinuria. In conclusion, in selected patients, combination antiviral therapy may still be a viable option postrenal transplant.